A quantitative role of rafting on low cycle fatigue behaviour of a directionally solidified Ni-based superalloy through a cross-correlated image processing method. (February 2020) - Fan, Y.S.; Yang, X.G.; Shi, D.Q.; Han, S.W.; Li, S.L.
Highlights: Rafting extent of the superalloy was quantitatively characterized by a cross-correlated image processing method. Rafting behaviour decreases the resistance to plastic deformation and the hardening effect of the γ ' precipitates, which promote the accumulation of the fatigue damage and reduce the fatigue life. A fatigue life prediction model considering the microstructural rafting was proposed, which is of good consistence with the experimental data. Abstract: Operating under elevated temperature and high stress for long terms, the regularly cubic γ ' precipitates of the Ni-based superalloy degrades to plate-like morphology perpendicular to the external stress. This process is called rafting and plays a deteriorated role on the mechanical properties of the alloy. In this study, the quantitative effect of rafting on the low cycle fatigue behaviour of a directionally solidified Ni-based superalloy was investigated. Fatigue tests were conducted at 850 °C with a 1.1% total strain range with six different rafting states. The fatigue life decreased considerably over 90% as the rafting state aggravated. The rafting process increased the width of the matrix channel, which weakened the plastic deformation resistance and the mean stress relaxation of the superalloy. To build a quantitative relationship between the life reduction and rafting state, a life prediction model was proposed based on the strengthening mechanism of Ni-based superalloys by assuming that the rafted alloy suffered a higher loading level compared with the virgin state. Moreover, the scanning electron microscopy was employed to observe fatigue fracture surfaces and the rafted microstructures. The micro-parameters such as the width of the γ ' precipitates and the matrix channel were obtained through a cross-correlated image processing method.